Cryo-EM structure and polymorphism of Aβ amyloid fibrils purified from Alzheimer’s brain tissue - Marius Kollmer (Nature Portfolio, 2019)
Alzheimer’s disease is characterised by the deposition of Aβ amyloid fibrils and tau protein neurofibrillary tangles. Here the authors use cryo-EM to structurally characterise brain derived Aβ amyloid fibrils and find that they are polymorphic and right-hand twisted, which differs from in vitro generated Aβ fibrils.